2020
DOI: 10.1186/s13643-020-01383-w
|View full text |Cite
|
Sign up to set email alerts
|

Latinx bullying and depression in children and youth: a systematic review

Abstract: Background: Bullying is associated with negative health outcomes such as depression. Most studies target non-Latinxs, though they often experience higher rates of bullying and depression. This review examines the inclusion of Latinxs in studies of bullying and depression and factors unique to them. Methods: Databases were searched for articles related to bullying and depression. Two reviewers found 957 publications and identified 17 for inclusion. Results: All 17 studies demonstrated a relationship between bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
2
11
0
4
Order By: Relevance
“…Our study is the first meta-analysis that includes 31 cross-sectional surveys focusing on the relationship between bullying behavior and depression in children and adolescents. Lutrick K [51] reported a positive relationship between being bullied and depression in children and adolescents through a meta-analysis, consistent with the results of the current study; however, their metaanalysis only evaluated the relationship between being bullied and depression in children and adolescents and focused on Latino populations, which are understudied. Recently, a meta-analysis conducted by Moore SE [52] found that bullying has negative impacts on mental health in children and adolescents, but the type of bullying examined was limited, and no systematic review of other types of bullying behavior has been conducted.…”
Section: Discussionsupporting
confidence: 87%
“…Our study is the first meta-analysis that includes 31 cross-sectional surveys focusing on the relationship between bullying behavior and depression in children and adolescents. Lutrick K [51] reported a positive relationship between being bullied and depression in children and adolescents through a meta-analysis, consistent with the results of the current study; however, their metaanalysis only evaluated the relationship between being bullied and depression in children and adolescents and focused on Latino populations, which are understudied. Recently, a meta-analysis conducted by Moore SE [52] found that bullying has negative impacts on mental health in children and adolescents, but the type of bullying examined was limited, and no systematic review of other types of bullying behavior has been conducted.…”
Section: Discussionsupporting
confidence: 87%
“…Because a substantial subset of Hispanic children in the United States are first- or second-generation immigrants ( 113 ), increased levels of depression in the Hispanic population might be related to migration stressors for first-generation youths ( 114 ), parental citizenship status ( 115 ), and cultural differences ( 116 ). However, they also might be associated with experiences related to racism and bias against cultural minorities, such as bullying experiences ( 117 , 118 ). At the same time, Hispanic children might be less likely than non-Hispanic children to access mental health care services, which might result in lower rates of diagnosis ( 119 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study results summarize that despite the type, bullying significantly decreases the HRQoL among adolescents [ 2 , 11 , 31 ], and that adolescents who were bullied repeatedly reported that it had a greater impact on their daily activities and social lives than did those who were not actively involved in bullying [ 21 , 32 ]. Furthermore, a negative impact of bullying on individuals’ moods and emotions [ 30 , 33 ] may also contribute to declines in HRQOL [ 22 ]. Due to bullying, adolescents feel shame, neglected by their social network/peers, and guilt, which lowers their self-esteem and self-perceptions [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study on Mexican adolescents [ 22 ] showed that bullied victims felt neglected by their peers and had low self-perceptions. Another disclosed bullying and depressive moods [ 33 ]. A few studies revealed an increased tendency among victims to attempt suicide [ 17 , 21 ], and one highlighted the high level of anxiety after being bullied [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation